Recent trends in maternal and child health inequalities in Latin America and the Caribbean: analysis of repeated national surveys - Oscar J. Mujica; Antonio Sanhueza; Liliana Carvajal-Velez; Luis Paulo Vidaletti; Janaína C. Costa; Aluísio J. D. Barros; Cesar G. Victora (BMC, 2023)
Abstract Background Although most Latin American and the Caribbean (LAC) countries made important progress in maternal and child health indicators from the 1990s up to 2010, little is known about such progress in the last decade. This study aims at documenting progress for each country as a whole, and to assess how within-country socioeconomic inequalities are evolving over time. Methods We identified LAC countries for which a national survey was available between 2011-2015 and a second comparable survey in 2018-2020. These included Argentina, Costa Rica, Cuba, the Dominican Republic, Guyana, Honduras, Peru, and Suriname. The 16 surveys included in the analysis collected nationally representative data on 221,989 women and 152,983 children using multistage sampling. Twelve health-related outcomes were studied, seven of which related to intervention coverage: the composite coverage index, demand for family planning satisfied with modern methods, antenatal care (four or more visits and eight or more visits), skilled attendant at birth, postnatal care for the mother and full immunization coverage. Five additional impact indicators were also investigated: stunting prevalence among under-five children, tobacco use by women, adolescent fertility rate, and under-five and neonatal mortality rates. For each of these indicators, average annual relative change rates were calculated between the baseline and endline national level estimates, and changes in socioeconomic inequalities over time were assessed using the slope index of inequality. Results Progress over time and the magnitude of inequalities varied according to country and indicator. For countries and indicators where baseline levels were high, as Argentina, Costa Rica and Cuba, progress was slow and inequalities small for most indicators. Countries that still have room for improvements, such as Guyana, Honduras, Peru and Suriname, showed faster progress for some but not all indicators, although also had wider inequalities. Among the countries studied, Peru was the top performer in terms of increasing coverage and reducing inequalities over time, followed by Honduras. Declines in family planning and immunization coverage were observed in some countries, and the widest inequalities were present for adolescent fertility and antenatal care coverage with eight or more visits. Conclusions Although LAC countries are well placed in terms of current levels of health indicators compared to most low- and middle-income countries, important inequalities remain, and reversals are being observed in some areas. More targeted efforts and actions are needed in order to leave no one behind. Monitoring progress with an equity lens is essential, but this will require further investment in conducting surveys routinely.